Paleomagnetic and geobarometric study of the mid-Cretaceous Whitehorse Pluton, Yukon Territory - Harris, M. J.; Symons, D. T. A.; Blackburn, W. H.; Hart, C. J. R. (Canadian Journal of Earth Sciences, 1997)
This is the first of several Lithoprobe paleomagnetic studies underway to examine geotectonic motions in the northern Canadian Cordillera. Except for one controversial study, estimates for terranes underlying the Intermontane Belt in the Yukon have been extrapolated from studies in Alaska, southern British Columbia, and the northwestern United States. The Whitehorse Pluton is a large unmetamorphosed and undeformed tonalitic body of mid-Cretaceous age (~112 Ma) that was intruded into sedimentary units of the Whitehorse Trough in the Stikinia terrane. Geothermobarometric estimates for eight sites around the pluton indicate that postmagnetization tilting has been negligible since cooling through the hornblende-crystallization temperature and that the pluton is a high-level intrusion. Paleomagnetic measurements for 22 of 24 sites in the pluton yield a well-defined characteristic remanent magnetization (ChRM) direction that is steeply down and northwards. The ChRM direction gives a paleopole of 285.5°E, 81.7°N (d p = 53°, d m = 5.7°). When compared with the 112 Ma reference pole for the North American craton, this paleopole suggests that the northern Stikinia terrane has been translated northwards by 11.0 ± 4.8° (1220 ± 530 km) and rotated clockwise by 59 ± 17°. Except for an estimate from the ~70 Ma Carmacks Group volcanics, this translation and rotation estimate agrees well with previous estimates for units in the central and southern Intermontane Belt. They suggest that the terranes of the Intermontane Belt have behaved as a fairly coherent unit since the Early Cretaceous, moving northward at a minimum average rate of 2.3 ± 0.4 cm/a between ~140 and ~45 Ma.